2021
DOI: 10.1097/pr9.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptors and neuropathic pain

Abstract: Growing evidence implicates the renin–angiotensin system (RAS) in multiple facets of neuropathic pain (NP). This narrative review focuses primarily on the major bioactive RAS peptide, Angiotensin II (Ang II), and its receptors, namely type 1 (AT1R) and type 2 (AT2R). Both receptors are involved in the development of NP and represent potential therapeutic targets. We first discuss the potential role of Ang II receptors in modulation of NP in the central nervous system. Ang II receptor expression is widespread i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 143 publications
1
13
0
Order By: Relevance
“…Components of the renin-angiotensin system (RAS) have been previously reviewed or discussed extensively [19,24,[58][59][60][61][62][63][64]. Nevertheless, the main findings are briefly summarized here for an overview.…”
Section: Endogenous Angiotensin Ligands and Angiotensin Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Components of the renin-angiotensin system (RAS) have been previously reviewed or discussed extensively [19,24,[58][59][60][61][62][63][64]. Nevertheless, the main findings are briefly summarized here for an overview.…”
Section: Endogenous Angiotensin Ligands and Angiotensin Receptorsmentioning
confidence: 99%
“…There is no clear consensus whether AT2Rs are expressed on sensory neurons creating a direct pharmacological target for analgesia [18,37,38,106,107,110], or the observed beneficial effect is mediated by immune cells infiltrating injured nerves [80,107]. The neuro-immune cross-talk proposed by the latter studies was recently reviewed by Balogh et al [19].…”
Section: At1 and At2 Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, physiological stimulation of the receptor causes diuresis and natriuresis by decreasing salt and water transport from the tubules to the capillaries, triggering sodium and water excretion ( 34 ). Chronic AT 2 R overexpression has deleterious effects on cardiomyocytes ( 35 ) and AT 2 R activation, as AT 1 R, is involved in neuropathic pain ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated circulating Ang II in the brain was reported to be associated with the genesis of arterial hypertension [ 8 ], whereas the overactivation of RAAS is crucially involved in the pathogenesis of hypertension and hypertension-related cardiovascular disorders [ 9 ]. Moreover, the beneficial effects of previous studies have shown that RAS blockers can reduce the development of hypertension and its associated neuropathic pain, cognitive impairment and cerebral injury [ 6 , 10 , 11 ]. By understanding role of the neuropeptides, opioids and angiotensin in CV function, we hope to trace the molecular origin of heart failure during the development of hypertension.…”
Section: Introductionmentioning
confidence: 99%